Reliability of balance evaluation using Pedalo®-Sensomove Balance device in healthy young individuals - GÜNAY YAZICI, CANAN; ÖZEN BERKOL, TUĞÇE; ÖZGÜL, BAHAR; KURU ÇOLAK, TUĞBA; SARI, ZÜBEYİR (My University, 2022)
Purpose: It is important to assess the integrity of the balance system to predict individual balance and coordination abilities. MarBES is a device consisting of 9 led scales and 4 pressure sensor systems developed to evaluate and improve balance and coordination as a TÜBİTAK 3001 project. Weight data is estimated from pressure sensors located in 4 different corners and a score is calculated with computer software for the individual\"s center of gravity (Centre of pressure X, Y) and the amount of deviation from the center for each axis.. The aim of this study is to examine the test-retest reliability of the MarBES device. Methods: Double-leg and single-leg (eyes open-closed) tests were applied to healthy young adult participants for balance testing on the MarBES device. Weight transfer to the target surface was measured for assessment of the participants coordination performance. Participants rested for 10 minutes and all measurements were repeated by the same evaluator. The obtained data were recorded and the reliability of the measurements was evaluated with Pearson correlation analysis. Results: A total of 33 healthy young individuals (24 F; 9 M) with a mean age of 21±0.96 years were included in the study. In the correlation analysis, there was a strong correlation in all measurement parameters of the MarBES device except for X axis measurements of right leg (eyes open) and double leg eyes closed (p<0.005). Conclusion: Objective evaluation of balance and coordination parameters is very important in rehabilitation. Resulde of the study showed that the MarBES device developed by the researchers is a reliable method for the evaluation of balance and coordination in healthy young individuals. Keywords: Balance, Coordination, Rehabilitation, Reliability
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation